2021
DOI: 10.1136/bcr-2020-241204
|View full text |Cite
|
Sign up to set email alerts
|

Response patterns for individuals receiving contingent skin shock aversion intervention to treat violent self-injurious and assaultive behaviours

Abstract: A small proportion of patients with intellectual disabilities (IDs) and/or autism spectrum disorder (ASD) exhibit extraordinarily dangerous self-injurious and assaultive behaviours that persist despite long-term multidisciplinary interventions. These uncontrolled behaviours result in physical and emotional trauma to the patients, care providers and family members. A graduated electronic decelerator (GED) is an aversive therapy device that has been shown to reduce the frequency of severe problem behaviours by 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Instead, Rodgers et al found poor quality studies at high risk of bias, leaving ignored ergo unknown harms balanced against uncertain and inconclusive evidence for benefits. Such "preventable uninformativeness" due to poor standards in intervention research has been flagged as a violation of research ethics, entailing de facto harms for study participants and the studied population (Zarin et al, 2019). In this way, the widespread promotion of early intensive autism interventions, based on the biased deployment of a literature uninformative about their benefits versus harms, has been and continues to be inherently harmful to autistics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, Rodgers et al found poor quality studies at high risk of bias, leaving ignored ergo unknown harms balanced against uncertain and inconclusive evidence for benefits. Such "preventable uninformativeness" due to poor standards in intervention research has been flagged as a violation of research ethics, entailing de facto harms for study participants and the studied population (Zarin et al, 2019). In this way, the widespread promotion of early intensive autism interventions, based on the biased deployment of a literature uninformative about their benefits versus harms, has been and continues to be inherently harmful to autistics.…”
mentioning
confidence: 99%
“…Negligent reporting, also unchallenged, serves to obscure the actual procedures used and at what intensity they may be applied for how much of an autistic's life. These distinctive failures plausibly underlie extreme practices, such as the use of skin shock, which, like other forms of physical punishment, is not a thing of the past for autistics (Yadollahikhales et al, 2021). Unacknowledged harms from an uninformative but influential autism intervention literature thus combine with the routine use and negligent reporting of plausibly harmful practices that accumulate and multiply, and lead to unethical extremes.…”
mentioning
confidence: 99%
“…Once the function of the behavior is determined, procedures such as extinction (decoupling the problem behavior from the consequence that gives it value, for example, by withholding attention following a vocal outburst), response blocking (physically preventing the enactment of the behavior), response cost (removing a positive reinforcement), or punishment (e.g. introducing an aversive event, such as a slap or electric shock) are used to decrease the occurrence of the problem behavior (Doehring et al, 2014;Yadollahikhales et al, 2021). Simultaneously, procedures such as prompting and reinforcement are used to teach and promote the use of alternative behaviors that could serve the same purported function as the problem behavior (Gregori et al, 2020).…”
Section: Addressing Problem Behaviormentioning
confidence: 99%
“…However, the task force report also noted that few studies have evaluated the long-term outcomes or side effects of CESS and that no studies have evaluated strategies for transferring control from CESS to other, less intrusive procedures. Most concerning, a retrospective analysis of clinical data collected across 20 years for 173 clients at the only facility to routinely use CESS found that it could be faded completely for just 27% of clients after more than 5 years of this treatment (Yadollahikhales et al, 2021 ). Most of these clients have continued to receive CESS indefinitely because the targeted behaviors increase when clinicians attempt to reduce or remove CESS from their treatment plans.…”
Section: Can Science On Cess Guide Us?mentioning
confidence: 99%